2009
DOI: 10.1016/j.theriogenology.2009.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cryopreservation on the motile sperm subpopulations in semen from Asturiana de los Valles bulls

Abstract: The aim of this study was to identify different motile sperm subpopulations in ejaculates from an autochthonous bull breed (Bos taurus) and to determine possible modifications in these subpopulations resulting from cryopreservation. Ejaculates were collected and cryopreserved following a conventional protocol. The overall sperm motility and the kinematic parameters of individual spermatozoa were evaluated in fresh ejaculates, after 4 h at 5 8C, and at 0 and 2 h postthaw. A multivariate clustering procedure sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
4
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 32 publications
(41 reference statements)
7
33
4
7
Order By: Relevance
“…There is paucity of literature on velocity distribution of motile sperm of frozen-thawed semen of buffalo bulls, however the present results corroborated with our recent report on crossbred (HF x K) bulls' semen (Patel and Dhami, 2013). Muino et al (2009) confirmed that there was a specific pattern of movement in each subpopulation of bull's ejaculate.…”
Section: Results and Discussion Casa Traits Of Fresh And Frozen-thawesupporting
confidence: 92%
“…There is paucity of literature on velocity distribution of motile sperm of frozen-thawed semen of buffalo bulls, however the present results corroborated with our recent report on crossbred (HF x K) bulls' semen (Patel and Dhami, 2013). Muino et al (2009) confirmed that there was a specific pattern of movement in each subpopulation of bull's ejaculate.…”
Section: Results and Discussion Casa Traits Of Fresh And Frozen-thawesupporting
confidence: 92%
“…In addition to the freezing rate mentioned above in Figure 1, other freezing rates can be found in different studies by other authors [2] [3] [4] [5] [6]. Among these alternative rates is, for example, a rate of 5°C/min between +5°C and -10°C, and 40°C/min between -10°C and -150°C, as shown in Figure 2, and a faster freezing rate of 60°C/min between +5°C and -120°C as shown in Figure 3 [6].…”
Section: Introductionmentioning
confidence: 82%
“…Bovine semen can be preserved using experimental freezing systems that use exposure to liquid nitrogen gases or through programmable automated freezing systems that can follow a certain pre-programmed rate of freezing. Most of the published works in relation to cryo-preservation [2] [3] [4] [5] [6] use programmable automated freezing systems that use different freezing rates (thermal descent velocity) as described below:…”
Section: Introductionmentioning
confidence: 99%
“…Sperm subpopulations in semen have been identified in different species on the basis of biochemistry (humans23), function (boars45), motility (stallions;6 red deer;78 dogs;9 bulls;10 rams;111213 and blue foxes14), and morphometry (stallions;15 boars;1617 red deer;718 bulls;1719 brown bears;20 rams;1213172122 Goeldi's monkey;23 and marmosets24). There is increasing evidence that the heterogeneity of these subpopulations has functional relevance.…”
Section: Introductionmentioning
confidence: 99%